1 ⋅ 2 ⋅ 3 ⋅ 4 1 + 2 ⋅ 3 ⋅ 4 ⋅ 5 1 + 3 ⋅ 4 ⋅ 5 ⋅ 6 1 + ⋯ till 50 terms = ?
Give your answer upto 4 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice solution :)
n = 1 ∑ 5 0 n ( n + 1 ) ( n + 2 ) ( n + 3 ) 1 = 6 1 n = 1 ∑ 5 0 ( n 1 − n + 1 3 + n + 2 3 − n + 3 1 ) 6 1 ( n = 1 ∑ 5 0 n 1 − 3 n = 1 ∑ 5 0 n + 1 1 + 3 n = 1 ∑ 5 0 n + 2 1 − n = 1 ∑ 5 0 n + 3 1 ) 6 1 ( n = 1 ∑ 5 0 n 1 − 3 n = 2 ∑ 5 1 n 1 + 3 n = 3 ∑ 5 2 n 1 − n = 4 ∑ 5 3 n 1 ) 6 1 ( 1 + 2 1 + 3 1 + 5 2 3 − 5 1 1 − 5 2 1 − 5 3 1 ) 6 1 ( 2 5 6 2 8 8 3 ) = 0 . 0 5 5 5
Yes, this is the standard Partial Fractions - Cover Up Rule method.
For a quicker method, you can do this (to get Atul Shivam's answer):
n ( n + 1 ) ( n + 2 ) ( n + 3 ) 1 = = = = 3 1 ⋅ n ( n + 1 ) ( n + 2 ) ( n + 3 ) 3 3 1 ⋅ n ( n + 1 ) ( n + 2 ) ( n + 3 ) n + 3 − n 3 1 ( n ( n + 1 ) ( n + 2 ) 1 − ( n + 1 ) ( n + 2 ) ( n + 3 ) 1 ) 3 1 ( T n − T n + 1 )
Apply telescoping sum, we get T 1 − T 5 1 as desired.
Log in to reply
Thank you for the explanation and the wiki link..
nice solution :)
The Cover Up Rule in Partial Fraction is the best method. However just as a different approach we have :-
n
=
1
∑
5
0
f
(
n
)
=
n
=
1
∑
5
0
n
(
n
+
1
)
(
n
+
2
)
(
n
+
3
)
1
.
L
e
t
t
=
n
2
+
3
n
+
1
.
∴
f
(
n
)
=
f
(
t
)
=
(
t
−
1
)
(
t
+
1
)
1
=
2
1
∗
{
t
−
1
1
−
t
+
1
1
}
S
u
b
s
t
i
t
u
t
i
n
g
b
a
c
k
n
f
o
r
t
,
f
(
n
)
=
2
1
∗
(
n
(
n
+
3
)
1
−
(
n
+
1
)
(
n
+
2
)
1
)
.
n
(
n
+
3
)
1
=
3
1
∗
{
n
1
−
n
+
3
1
}
a
n
d
(
n
+
1
)
(
n
+
2
)
1
,
we can calculate directly since (n+2)=(n+1) +1 .
∴
n
=
1
∑
5
0
f
(
n
)
=
n
=
1
∑
5
0
6
1
∗
(
n
1
−
n
+
3
1
)
−
2
1
∗
(
n
+
1
1
−
n
+
2
1
)
In the first group,
from n to n+3 , first three of n,
and last three of n+3 are only term not canceling
.
⟹
n
=
1
∑
5
0
f
(
n
)
=
6
1
∗
(
1
1
+
2
1
+
3
1
−
5
1
1
−
5
2
1
−
5
3
1
)
−
2
1
∗
(
2
1
−
5
1
1
)
=
0
.
0
5
5
7
4
1
Problem Loading...
Note Loading...
Set Loading...
Hint: apply telescopic series to get the result for sum of n terms which is S n = 3 1 [ 1 × 2 × 3 1 − ( n + 1 ) ( n + 2 ) ( n + 3 ) 1 ] and hence put n = 5 0 to get sum equal to 0 . 0 5 5